Early Outcomes With Cerebral Embolic Protection During Transcatheter Aortic Valve Replacement in Patients With Atrial Fibrillation - Shashank Shekhar, MD; Amar Krishnaswamy, MD; Grant Reed, MD, MSc; James Yun, MD; Rishi Puri, MD, PhD; Samir Kapadia, MD (Structural Heart)
Background: Limited studies are available which aim to identify patient populations that would potentially benefit from the use of cerebral embolic protection devices (CPDs) during transcatheter aortic valve replacement (TAVR). We aimed to analyze the impact of CPD use during TAVR among patients with atrial fibrillation (AF). Methods: Data on adult TAVR patients with a concomitant diagnosis of AF was obtained from the 2017-2020 National Readmissions Database. Stroke, major stroke, in-hospital mortality, and 30-day readmission rates were compared between the CPD and no-CPD cohorts in a propensity score matched analysis. Association of CPD use with adverse events was analyzed using multivariable logistic regression models. Results: Of 100,928 eligible TAVR patients with AF, CPD was used in 6.9% of patients with a mean age of 80 years. CPD use was independently associated with lower overall stroke (1.7% vs. 2.2%; odds ratio [OR] 0.81 [95% CI 0.68-0.98]; p = 0.032), major stroke (1.2% vs. 1.8%; OR 0.69 [0.55-0.86]; p = 0.001), in-hospital mortality (0.9 vs. 1.5%; OR 0.56 [0.43-0.72]; p < 0.001), and lower 30-day readmission rates (12.7% vs. 14.7%; OR 0.87 [0.81-0.94]; p < 0.001). Reduction in adverse events with CPD was noted in high-volume but not in low-volume TAVR centers. Conclusions: The present point towards clear benefits of CPD use among patients with AF undergoing TAVR. In anatomically eligible patients, the potential benefit of debris capture may be considered especially as younger and lower risk patients become eligible for TAVR. Data from future trials and registries are required to further corroborate our findings.